DNA Adenine Methyltransferase (Dam) Overexpression Impairs Photorhabdus luminescens Motility and Virulence - Payelleville, Amaury; Lanois, Anne; Gislard, Marie; Dubois, Emeric; Roche, David; Cruveiller, Stéphane; Givaudan, Alain; Brillard, Julien (Frontiers in Microbiology, 2017)
Dam, the most described bacterial DNA-methyltransferase, is widespread in gamma-proteobacteria. Dam DNA methylation can play a role in various genes expression and is involved in pathogenicity of several bacterial species. The purpose of this study was to determine the role played by the dam ortholog identified in the entomopathogenic bacterium Photorhabdus luminescens. Complementation assays of an Escherichia coli dam mutant showed the restoration of the DNA methylation pattern of the parental strain. Overexpression of dam in P. luminescens did not impair growth ability in vitro. In contrast, compared to a control strain harboring an empty plasmid, a significant decrease in motility was observed in the dam-overexpressing strain. A transcriptome analysis revealed the differential expression of 208 genes between the two strains. In particular, the downregulation of flagellar genes was observed in the dam-overexpressing strain. In the closely related bacterium Xenorhabdus nematophila, dam overexpression also impaired motility. In addition, the dam-overexpressing P. luminescens strain showed a delayed virulence compared to that of the control strain after injection in larvae of the lepidopteran Spodoptera littoralis. These results reveal that Dam plays a major role during P. luminescens insect infection.